2011
DOI: 10.1245/s10434-011-1560-3
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparison of the Prognostic Value of Tumor- and Patient-Related Factors in Patients Undergoing Potentially Curative Surgery for Pancreatic Ductal Adenocarcinoma

Abstract: We have prospectively validated the influence of tumor-related and patient-related factors. Margin involvement and the preoperative mGPS were the most important determinants of overall survival in patients undergoing potentially curative pancreaticoduodenectomy. Furthermore, both had independent prognostic value in those patients receiving adjuvant chemotherapy. In the future, this may be considered a stratification factor for entry onto therapeutic trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 42 publications
6
77
2
3
Order By: Relevance
“…14,49 However, the topic of debate is in choosing the right cut-off point for tumor diameter and many studies have already assessed and the most reported size cut-offs ranged from 2cm to 3 cm. 10,17,[51][52][53][54] In our present study, the greatest impact of tumor size was seen on tumors below and above 2 cm with median survival of 41.02 months vs. 16.20 months respectively. However, for the larger tumor size the results is found to be less appealing, may be due to lesser number of studies and trials as in the present study we were able to include only 2 studies reporting survival outcome of tumors less or more than 4 cm.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…14,49 However, the topic of debate is in choosing the right cut-off point for tumor diameter and many studies have already assessed and the most reported size cut-offs ranged from 2cm to 3 cm. 10,17,[51][52][53][54] In our present study, the greatest impact of tumor size was seen on tumors below and above 2 cm with median survival of 41.02 months vs. 16.20 months respectively. However, for the larger tumor size the results is found to be less appealing, may be due to lesser number of studies and trials as in the present study we were able to include only 2 studies reporting survival outcome of tumors less or more than 4 cm.…”
Section: Discussionsupporting
confidence: 47%
“…33,37 Various published reports supported the fact that smaller tumors have comparatively better survival outcome than larger tumors and the cut-off points ranged from 2cm to 3cm. 17,49,[51][52][53] Yeo et al 9 reported a 5-year survival of 28% for tumor size less than 3 cm and 15% for tumor size more than 3 cm. Similarly, Petermann et al 14 reported a median survival of 40.8 months and 15.6 months for tumors less than 2 cm and more than 2 cm respectively, which was very similar to our result.…”
Section: Discussionmentioning
confidence: 99%
“…When we examine outcomes for resectable pancreatic ductal adenocarcinoma (PDAC) we find similar results in 2 studies of 135 patients from Glasgow [10] and 102 patients from Rome [11] Table 3. Each group of surgeons reported much better survival for GPS ¼ 0 ranging from 26.7 to 37.2 months and significantly poorer survivals for those with preoperative GPS of 1 (11.5e16.5 months) and GPS ¼ 2 (only 7.3e13.1 months).…”
Section: Sir In Pancreatic Cancermentioning
confidence: 57%
“…14 of the remaining 35 studies (Kim et al, 2006;Murakami et al, 2008;Balentine et al, 2010;Chu et al, 2010;Kanda et al, 2010;de Jong et al, 2011;Jamieson et al, 2011;Kneuertz et al, 2011;Maithel et al, 2011;Singal et al, 2011;Chatterjee et al, 2012;Watanabe et al, 2012;Xie et al, 2012;Fisher et al, 2013) were excluded because they were reported by the same institutions as other studies. 21 studies (Ozaki et al, 1999;Mitsunaga et al, 2005;Nakagohri et al, 2006;Pawlik et al, 2007;Kazanjian et al, 2008;Kato et al, 2009;Nagai et al, 2009;Sergeant et al, 2009;Ben et al, 2010;Murakami et al, 2010;Bachellier et al, 2011;Kim et al, 2011;Schiffman et al, 2011;Cheng et al, 2012;Jamieson et al, 2012;Lee et al, 2012;Murata et al, 2012;Sahin et al, 2012;Takahashi et al, 2012;Turrini et al, 2013;Xie et al, 2013) were included in the final meta-analysis, comprising one case matched controlled study and 20 retrospective cohort studies (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%